Analysis of Antibiotic Use Pattern in Patient With Acute Respiratory Tract Infection at Royal Prima Hospital Medan Year 2023 - 2024 - Amalia Fizry Munthe; Suhartina Darmadi; Sri Lestari (International Journal of Health and Pharmaceutical (IJHP), 2025)
. Acute Respiratory Tract Infection (ARTI) remains one of the leading causes of morbidity in Indonesia, particularly among children and toddlers. Irrational use of antibiotics continues to be a serious issue as it contributes to the growing problem of antimicrobial resistance. Therefore, this research tended to analyze the pattern of antibiotic use among ARTI patients at Royal Prima Hospital Medan during the period of 2023–2024. This study employed a descriptive quantitative design with a cross-sectional approach. Data were collected retrospectively from the medical records of 211 patients diagnosed with ARTI who were treated at Royal Prima Hospital Medan. The variables analyzed included patient characteristics (age and gender), type of ARTI, type and class of antibiotics, and duration of antibiotic administration. Data were processed and analyzed using SPSS version 25 descriptively in the form of percentage distributions and frequency. The results showed that most ARTI patients were male (55.5%), and belonged to the toddler (55.0%) and child (37.9%) age groups. The most common type of ARTI found was upper respiratory tract infection (bronchitis, pharyngitis, sinusitis, and laryngitis), accounting for 89.3% of cases. A total of 91.5% of patients received antibiotics, while 8.5% did not. The most frequently used antibiotic was amoxicillin (46.9%), followed by cefixime (25.1%). Based on the WHO AWaRe classification (2023), ACCESS group antibiotics dominated usage (>60%), while WATCH group antibiotics were used in limited cases (25%). The most common duration of antibiotic therapy was 3–5 days, and most patients received monotherapy (85.8%). Overall, the pattern of antibiotic use among ARTI patients at Royal Prima Hospital Medan was largely in accordance with WHO and Indonesian Ministry of Health guidelines, particularly in the selection of ACCESS group antibiotics and the limitation of combination therapy. However, the high rate of antibiotic prescription for mild ARTI cases indicates the need to strengthen the Antimicrobial Resistance Control Program (PPRA) and implement delayed antibiotic prescription strategies to develop the antibiotics’ rational use in hospital settings.